Stress-related Disorders in Health-care Workers in COVID-19 Pandemic: A Cross-Sectional Study from India - Surabhi Mathur; Divya Sharma; Ram Kumar Solanki; Manish Kumar Goyal (Indian Journal of Medical Specialities)
Background: The coronavirus disease-2019 (COVID-19) outbreak, first detected in Wuhan, China, has turned into a rapidly spreading pandemic ailing the human race throughout the world. Health-care workers (HCWs) are under immense physical and psychological pressure, adversely affecting their efficiency and decision making. Aim: We hereby intend to study the impact of COVID-19 pandemic in HCWs in reference with a variety of factors. Materials and Methods: A nationwide cross-sectional online study using semi-structured pro forma along with the Adjustment Disorder New Module and the Depression, Anxiety, and Stress Scale-21 was conducted among 200 respondents. Results and Discussion: Of the 200 respondents, 174 (87%) were doctors and 26 nursing staff, with a mean age of 42.1 ± 12.2 years, 62% were male, and 63% were working in the government sector. A significant number of respondents were found to be suffering from acute stress (9.5%), depression (17%), and anxiety (19.5%) which they attributed to the negative professional and personal influence of this ongoing pandemic scenario. HCWs on the front lines of this pandemic are facing compounding stressors and need robust psychiatric help to adequately take care of this need.